Epidemiological characteristics of methicillin-resistant Staphylococcus aureus isolates from bloodstream cultures at University Hospital in the Czech Republic - Neradova, Katerina; Fridrichova, Marta; Jakubu, Vladislav; Pomorska, Katarina; Zemlickova, Helena (Folia microbiologica, 2020)
The aim of this study was to trace the dynamic changes of methicillin-resistant Staphylococcus aureus (MRSA) lineages in the local hospital in both the national and international context. We describe genotypic and phenotypic characterization of 62 non-duplicate MRSA isolates collected during 2010-2016 at University Hospital in Hradec Kralove, Czech Republic. The isolates were characterized by multilocus sequence typing (MLST), spa typing, and staphylococcal cassette chromosome mec typing (SCCmec typing). Eight different genotypes were described; ST225-t003-II (32/62, 52%), ST5-t002-II (13/62, 22%), and ST225-t014-II (12/62, 21%) were constantly detected over the 7-year follow-up period. The genotypes ST225-t151-II, ST225-t1282-II, ST225-t1623-II, ST78-t2832-II, and ST225-t8799-II occurred only once in the period reported. The majority of the strains, represented by ST225, belonged to clonal complex 5 (CC5).
Keywords: dospělí; Genotype; Female; Phenotype; Infant; Hospitals, University; mikrobiální testy citlivosti; dítě; předškolní dítě; Adult; ženské pohlaví; mladý dospělý; Adolescent; lidé; genotyp; Anti-Bacterial Agents; multilokusová sekvenční typizace; Bacteremia; Aged, 80 and over; methicilin rezistentní Staphylococcus aureus; bakteriemie; Microbial Sensitivity Tests; stafylokokové infekce; Male; kojenec; Aged; Czech Republic; Child, Preschool; Young Adult; Bacterial Typing Techniques; techniky typizace bakterií; Česká republika; Multilocus Sequence Typing; lidé středního věku; nemocnice univerzitní; senioři nad 80 let; Child; senioři; mužské pohlaví; fenotyp; Staphylococcal Infections; antibakteriální látky; Middle Aged; mladiství; Methicillin-Resistant Staphylococcus aureus; Humans